Development of optimal participating strategy for source‐grid‐load‐storage integrated projects in electricity markets with multi‐stage joint optimization - Zihao Li; Yu Yang; Yifan Shi; Li Yao; Wei Liu; Fushuan Wen (IET Renewable Power Generation)
Abstract To promote peer‐to‐peer trading in a distribution system with the franchise owned by the concerned distribution company respected, a so‐called “source‐grid‐load‐storage” (SGLS) integrated project is promoted in China. Given this background, this paper proposes a multi‐stage joint optimization model to optimize the participating strategy for SGLS‐IPs in electricity energy and ancillary service markets. A multi‐energy flow park model is presented with electricity, gas, and heat included. A two‐stage model for optimal participating strategy of SGLS‐IPs in electricity and ancillary service markets is then presented. Through scenario analysis of a sample system, the attained revenue of an SGLS‐IP in different markets is evaluated. Additionally, a bilevel Stackelberg game model is introduced for internal electric vehicle clusters (EVCs) within an SGLS‐IP, with the upper level representing an SGLS‐IP, and the lower level representing EV users engaging in the game. The effectiveness of the model is validated through case studies. Simulation results demonstrate that reasonable market participation and pricing strategies contribute to the efficient allocation of resources within a SGLS‐IP and a win‐win outcome for both the SGLS‐IP entity and EV users.